The effect of the application of the think talk write model and self-efficacy on students' critical thinking ability in the material reaction rate in SMA Adhyaksa 1 Jambi city - Intan Aulia Sari; Haryanto Haryanto; Yusnaidar Yusnaidar (Jurnal Pendidikan Kimia (JPKIM), 2022)
The ability to think critically is very important to support the progress of education. In developing good mastery of learning concepts, students' critical thinking skills are needed. The development of critical thinking skills can make students give up, so it takes a firm belief in students' abilities in overcoming difficulties so they can become more advanced. This study aims to see the effect of the Think Talk Write (TTW) and Self Efficacy on students' critical thinking skills in the matter of reaction rate. The sample used consisted of 2 classes at SMA Adhyaksa 1 Jambi City. The data collection instruments used were observation sheets, self-efficacy, and essay tests. The data analysis used was 2-way ANOVA. The results showed that learning using the TTW and Self Efficacy affected students' critical thinking skills with an average of 71% from meeting 1, meeting 2, and meeting 3. Then there is an interaction between the Think Talk Write and Self Efficacy on students' critical thinking skills seen from a significance value of 0.000 <0.05.Keywords:Critical thinking; Reaction rate; Self-efficacy; Think talk write